T213. TREND OF LONG-ACTING INJECTABLE ANTIPSYCHOTICS USE IN ASIA: FINDINGS FROM REAP ANTIPSYCHOTIC STUDIES. (18th May 2020) - Lin, Shih-Ku; Chung, An-Nie
Abstract: Background: Research on Asian Prescription Pattern (REAP) is the largest and the longest lasting international collaborative research in psychiatry in Asia since 2001. At present, four studies on antipsychotics in schizophrenia, two antidepressants, one bipolar disorder and one mood disorder were completed. Previous studies have examined the use of Long-acting Injectable (LAI) antipsychotic in patients with schizophrenia and revealed major differences across countries. The aim of the study is to investigate the prescription trend of LAI antipsychotic use in four REAP schizophrenia surveys. Methods: We analyzed the results from four times of REAP studies (AP1 to AP4, 2001, 2004, 2009 and 2016), to compare the trend of LAI prescriptions rates in China, Hong Kong, Japan, Korea, Singapore, and Taiwan, and also the rate of LAI use among 15 Asian countries in AP4. Results: A total of 10505 patients were analyzed, with an average rate of 14.6% of patients received LAI antipsychotic treatment. For comparison of AP1 to AP4, there was a wide variation in the rate of LAI use among the six countries, with the highest prescription rate in Singapore (68.1%) and the lowest in Korea (1.6 %). Korean patients received no LAIs treatment in the first two surveys, and the rates in China and Japan were also very low. While in Hong Kong and Singapore, the rates were much higher. In AP4 survey, India, Malaysia, Thailand, Pakistan and Sri Lanka have a higher rate of LAI use, while in Indonesia, Myanmar, the rate is much lower. Vietnam does not use LAI at all. The prescription trend was also diverse, which increased in Korea and Japan and decreased in China, Hong Kong and Singapore. The overall prescription trend of LAI was in decrease. Besides, when analyzing cases with only using second generation antipsychotics, the usage of LAI was increased. Discussion: Previous studies identified several factors associated with prescription of LAI, including demographic and clinical characteristics of patients, patients' and physicians' attitude towards LAI, availability of LAI, insurance coverage and related cultural factors. The prescription trend of first generation LAI was decreased in most of the six countries; on the other hand, second generation LAI usages maintain steady level and even slightly increased. In conclusion, LAI antipsychotic is still underuse in Asia, especially in some countries such as Korea, China, Japan, Indonesia and Myanmar. Various factors that influenced the prescription rate of LAI antipsychotic should be addressed further.